ROLE OF TRIMETAZIDINE, A CYTOPROTECTIVE AGENT IN ISCHEMIC HEART DISEASE - Kaur, Sharanjit; Singh, Harinder Jot; Nayyar, Sanjay; Kaur, Navpreet; Manzoor, Sami (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Metabolic agents such as trimetazidine offer a benefits role of cytoprotection in ischemic heart disease (IHD) through an inhibition of cardiac fatty acid oxidation and improving myocardial glucose utilization. To show the efficacy of trimetazidine in reducing the incidence of angina and improving exercise tolerance. Methods: 50 diagnosed cases of chronic stable angina taking conventional treatment were subjected to stress test (treadmill) on day 0 to evaluate the parameters such as effort duration and ST-segment changes at the end of the exercise. After evaluation, the patients will be given trimetazidine for a period of 6-week at a dosage of 60 mg (in three divided doses) daily. After completion of the stipulated period, a second stress test evaluation was done. Results: The present study consisted of 50 patients of chronic stable angina, out of which 35 were males and 15 were female patients. It was seen that trimetazidine intake brought about an increase in the mean exercise time from 7.086Â±0.96 to 8.3Â±0.75 and showed good symptomatic improvement (in 31 patients). 15 patients did not show any appreciable (>1 minute) increase in the effort duration. No severe symptoms were reported to warrant discontinuation of the drug. Conclusion: Trimetazidine is an effective anti-anginal as monotherapy as well as an adjuvant to conventional anti-anginals as a cytoprotective agent. Keywords: Trimetazidine, Cytoprotective, Metabolic modulator, Ischemic heart disease.